A novel non-canonical WNT pathway regulates the asymmetric b cell division in Caenorhabditis elegans - Wu, Mingfu (Kansas State University, 2007)
The polarities of several cells that divide asymmetrically during C. elegans development are controlled by Wnt signaling. LIN-44/Wnt and LIN-17/Fz control the polarities of cells in the tail of developing C. elegans larvae, including the male-specific blast cell, B, which divides asymmetrically to generate a larger anterior daughter and a smaller posterior daughter. We determined that the canonical Wnt pathway components are not involved in the control of B cell polarity. However, POP-1/Tcf is involved and asymmetrically distributed to B daughter nuclei. Aspects of the B cell division are reminiscent of the divisions controlled by the planar cell polarity (PCP) pathway that has been described in both Drosophila and vertebrate systems. We identified C. elegans homologs of Wnt/PCP components and have determined that many of them appear to be involved in the regulation of B cell polarity and POP-1 asymmetric distribution to B daughter nuclei. Thus a non-canonical Wnt pathway, which is different from other Wnt pathways in C. elegans, but similar to the PCP pathways, appears to regulate B cell polarity. Molecular mechanisms of this PCP pathway were also investigated. We determined that LIN-17/Fz is asymmetrically distributed to the B cell cortex prior to, during, and after, division. Furthermore, the asymmetric localization of LIN-17:GFP is controlled by LIN-44/Wnt and MIG-5/Dsh. The cysteine rich domain (CRD), seven trans-membrane domain and KTXXXW motif of LIN-17 are required for LIN-17 to rescue lin-17, while only seven trans-membrane domains and KTXXXW motif are required for LIN-17 asymmetric localization. MIG-5:GFP asymmetrically localized to the B cell prior to and after division in a LIN-17/Fz dependent manner. We examined the functions of these MIG-5 domains. The DEP domain is required for MIG-5 membrane association, while the PDZ domain is responsible for different levels of MIG-5 in the B daughters. The DEP and PDZ domain are required to rescue B cell polarity defect of mig-5 males, while the DIX domain is not that important. In summary, a novel PCP-like pathway, in which LIN-17 and MIG-5 are asymmetrically localized, is conserved in C. elegans and involved in the regulation of B cell polarity.
Keywords: Planar cell polarity; Wnt signaling; Frizzled/Fz; Asymmetric cell division; Dishevelled/Dsh; Biology, Cell (0379); Biology, Genetics (0369); Biology, Molecular (0307)